Learner’s English Proficiency and their Pragmatic Competence of Refusal Speech Acts - Tabatabaei, Soudabeh; Farnia, Maryam (Widya Mandala Catholic University Surabaya, 2015)
Abstract The present study is an attempt to investigate the relationship between language proficiency and ‎pragmatic comprehension of the refusal speech act among Iranian EFL learners. To this end, the ‎Oxford Placement Test (OPT), as a proficiency test, was given to participants and they were ‎divided into high and low level groups based on their proficiency scores. Then, a multiple-choice ‎discourse completion task (MDCT) was given to both groups to elicit their pragmatic ‎knowledge. The findings indicated that there was no significant ‎difference between high and low groups in pragmatic comprehension. In other words, language ‎proficiency was not the determining factor in the degree of pragmatic comprehension. Moreover, the results indicated that there was no correlation between learners’ language proficiency and pragmatic knowledge. Therefore, ‎in order to have pragmatically competent EFL learners, they should be taught pragmatic functions and language norms of the target language in the language classrooms. Keywords: Pragmatic comprehension, Speech acts, Refusal speech act, MDCT.